The Effects of a Diabetic Self-management Program on Knowledge, Behavior, and Health Indexes among People with Type 2 Diabetes - Ratanapitak, Uranee; Krainuwat, Kerada; Sriwijitkamol, Apiradee; Vipawattana, Chutatip (Nursing Science Journal of Thailand, 2013)
Purpose: This study aimed to assess the effects of a diabetic self-management program on knowledge, behavior, and health indexes among people with type 2 diabetes. Design: Experimental study design. Methods: 117 people with type 2 diabetes were participated in the study. Participants were randomly selected from the population and randomly assigned into an intervention or a control group. Of all participants, 59 participants were in the intervention group (receiving a diabetic self-management program based on precede-proceed model and self-efficacy theory) and 58 were in the control group (receiving routine care). Data were collected by self-reported questionnaires and self-recorded diary. Data were analyzed using descriptive statistics (percentile, mean and standard deviation), and inferential statistics (t-test, chi-square, and repeated-measures analysis of variance). Main findings: The findings showed that participants in the intervention group gained better knowledge, behavior, fasting blood sugar, and HbA1C than participants in the control group significantly. This diabetic self-management program was effective and had a medium to strong effect size and participants in the intervention group were able to maintain their healthy behavior for 18 months. Conclusion and recommendations: Knowledge, skills training, nurse support including home visit, and self-efficacy were the cornerstone of this diabetic self-management program. It fostered people with type 2 diabetes to be able to control the level of fasting blood sugar and HbA1C. This program could be applied for other similar health care agencies. Keywords: behavior, health index, knowledge, self-management program, type 2 diabetes บทคัดย่อ วัตถุประสงค์: เพื่อประเมินผลของโปรแกรมการจัดการเบาหวานด้วยตนเองต่อระดับความรู้ พฤติกรรมและดัชนี สุขภาพของผู้เป็นเบาหวานชนิดที่ 2 รูปแบบการวิจัย: การวิจัยเชิงทดลอง วิธีการดำเนินการวิจัย: ผู้เป็นเบาหวานชนิดที่ 2 ที่มีคุณสมบัติตามเกณฑ์ถูกสุ่มเข้าเป็นกลุ่มตัวอย่างจำนวน 117 คน และได้รับการสุ่มเข้าสู่กลุ่มทดลอง 59 คนและกลุ่มควบคุม 58 คน โดยกลุ่มทดลองได้รับโปรแกรมการจัดการเบาหวานด้วยตนเองภายใต้กรอบแนวคิด precede-proceed model และ self-efficacy ขณะที่กลุ่มควบคุมได้รับการดูแลตามปกติ เก็บข้อมูลจากการตอบแบบสอบถามและการจดบันทึก วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณา (ร้อยละ ค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐาน) และสถิติอ้างอิง (t-test, chi-square, repeated-measures analysis of variance) ผลการวิจัย: กลุ่มทดลองมีความรู้ พฤติกรรม น้ำตาลในเลือด น้ำตาลสะสมดีกว่ากลุ่มควบคุมอย่างมีนัยสำคัญ โปรแกรมมีค่าขนาดอิทธิพลปานกลางถึงสูง ผู้เป็นเบาหวานในกลุ่มทดลองสามารถรักษาพฤติกรรมสุขภาพคงอยู่นาน 18 เดือน สรุปและข้อเสนอแนะ: การให้ความรู้คู่กับการฝึกทักษะ การสนับสนุนของพยาบาลรวมถึงการเยี่ยมบ้านและการสร้างเสริมสมรรถนะแห่งตนเป็นแกนสำคัญของโปรแกรมการจัดการเบาหวานด้วยตนเอง โปรแกรมช่วยให้ผู้เป็นเบาหวานควบคุมน้ำตาลในเลือดและน้ำตาลสะสมได้ดี ผลของโปรแกรมสามารถประยุกต์ใช้ในหน่วยงานอื่นที่คล้ายคลึงกันได้ คำสำคัญ: พฤติกรรม ดัชนีสุขภาพ ความรู้ โปรแกรมการจัดการตนเอง ผู้เป็นเบาหวานชนิดที่ 2